Effect of Ethanolic Extract of Seeds of Solanum torvum in Acetic Acid induced Ulcerative Colitis in Male Wistar Rats - N.S.R. Bhargavi; Sushma Poojari; Mahalaxmi Mohan (Journal of Basic & Applied Sciences, 2019)
Objective: To elucidate the protective effect of ethanolic extract of dried seeds of Solanum torvum (S. torvum) in acetic acid-induced ulcerative colitis in male Wistar rats. Methods: The animals were divided into various treatment groups (n=5). Rats were administered with 2ml of acetic acid (4%) via intrarectal route. Prednisolone was used as a standard drug and S. torvum was administered at a dose of 100 and 300mg/kg, p.o. Macroscopic score, colon weight to length ratio, colonic superoxide dismutase (SOD), reduced glutathione (GSH), myeloperoxidase (MPO), catalase (CAT), and lipid peroxidation (TBARS) levels and histopathological changes were recorded after the treatment regimen of 11 days. Results: Intrarectal instillation of acetic acid caused significant (P<0.05) increase in colon weight to length ratio, TBARS, and MPO levels. It caused significant (P<0.05) decrease in the levels of SOD, CAT and GSH levels. Pretreatment with S. torvum (100&300mg/kg, p.o.) exhibited significant (p<0.05) increase in the levels of SOD, CAT and reduced GSH and significant decrease in TBARS and MPO levels. Histopathological changes showed that acetic acid treatment caused significant structural damage to colon like inflammation, ulceration with a loss of 40% mucosa which was reversed by S. torvum (100&300mg/kg) treatment. Conclusion: The present investigation demonstrates the potent therapeutic value of S.torvum (100, 300 mg/kg, p.o.) in the amelioration of experimental ulcerative colitis in rats.